The connection between star formation and supermassive black hole activity in the local Universe. Issue 2 (28th June 2021) - Torbaniuk, O; Paolillo, M; Carrera, F; Cavuoti, S; Vignali, C; Longo, G; Aird, J
ABSTRACT: We study the nuclear (AGN) activity in the local Universe ( z < 0.33) and its correlation with the host galaxy properties, derived from a Sloan Digital Sky Survey sample with spectroscopic star-formation rate (SFR) and stellar mass determination. To quantify the level of AGN activity we used the XMM-Newton Serendipitous Source Catalogue. Applying multiwavelength selection criteria (optical BPT-diagrams, X-ray/optical ratio etc), we found that 24 per cent of the detected sources are efficiently-accreting AGN with moderate-to-high X-ray luminosity, twice as likely to be hosted by star-forming galaxies than by quiescent ones. The distribution of the specific Black Hole accretion rate (λsBHAR ) shows that nuclear activity in local, non-AGN dominated galaxies peaks at very low accretion rates (−4 ≲ log λsBHAR ≲ −3) in all stellar mass ranges. We observe systematically larger values of λsBHAR for galaxies with active star formation than for quiescent ones, and an increase of the mean λsBHAR with SFR for both star-forming and quiescent galaxies. These finding confirm the decrease in AGN activity with cosmic time and are consistent with a scenario where both star-formation and AGN activity are fuelled by a common gas reservoir.